Measurement of the cross-section of high transverse momentum vector bosons reconstructed as single jets and studies of jet substructure in pp collisions at s√ = 7 TeV with the ATLAS detector - Aad, G. (2014)
This paper presents a measurement of the cross-section for high transverse momentum W and Z bosons produced in pp collisions and decaying to all-hadronic final states. The data used in the analysis were recorded by the ATLAS detector at the CERN Large Hadron Collider at a centre-of-mass energy of √ s = 7 TeV and correspond to an integrated luminosity of 4 .6 fb − 1 . The measurement is performed by reconstructing the boosted W or Z bosons in single jets. The reconstructed jet mass is used to identify the W and Z bosons, and a jet substructure method based on energy cluste r information in the jet centre-of-mass frame is used to suppress the large multi-jet background. The cross-section for events with a hadronically decaying W or Z boson, with transverse momentum p T > 320 GeV and pseudorapidity |η| < 1 . 9, is measured to be σ W + Z = 8 . 5 ± 1 . 7 pb and is compared to the next-to-leading-order calculations. The selected events are further used to study jet grooming techniques.